A validation of the application of D2O stable isotope tracer techniques for monitoring day-to-day changes in muscle protein subfraction synthesis in humans - Wilkinson, Daniel J.; Franchi, Martino V.; Brook, Matthew S.; Narici, Marco V.; Williams, John P.; Mitchell, William K.; Szewczyk, Nathaniel J.; Greenhaff, Paul L.; Atherton, Philip J.; Smith, Kenneth (American Physiological Society, 2014)
Quantification of muscle protein synthesis (MPS) remains a cornerstone for understanding the control of muscle mass. Traditional [13C]amino acid tracer methodologies necessitate sustained bed rest and intravenous cannulation(s), restricting studies to ∼12 h, and thus cannot holistically inform on diurnal MPS. This limits insight into the regulation of habitual muscle metabolism in health, aging, and disease while querying the utility of tracer techniques to predict the long-term efficacy of anabolic/anticatabolic interventions. We tested the efficacy of the D2O tracer for quantifying MPS over a period not feasible with 13C tracers and too short to quantify changes in mass. Eight men (22 ± 3.5 yr) undertook one-legged resistance exercise over an 8-day period (4 × 8–10 repetitions, 80% 1RM every 2nd day, to yield “nonexercised” vs. “exercise” leg comparisons), with vastus lateralis biopsies taken bilaterally at 0, 2, 4, and 8 days. After day 0 biopsies, participants consumed a D2O bolus (150 ml, 70 atom%); saliva was collected daily. Fractional synthetic rates (FSRs) of myofibrillar (MyoPS), sarcoplasmic (SPS), and collagen (CPS) protein fractions were measured by GC-pyrolysis-IRMS and TC/EA-IRMS. Body water initially enriched at 0.16–0.24 APE decayed at ∼0.009%/day. In the nonexercised leg, MyoPS was 1.45 ± 0.10, 1.47 ± 0.06, and 1.35 ± 0.07%/day at 0–2, 0–4, and 0–8 days, respectively (∼0.05–0.06%/h). MyoPS was greater in the exercised leg (0–2 days: 1.97 ± 0.13%/day; 0–4 days: 1.96 ± 0.15%/day, P < 0.01; 0–8 days: 1.79 ± 0.12%/day, P < 0.05). CPS was slower than MyoPS but followed a similar pattern, with the exercised leg tending to yield greater FSRs (0–2 days: 1.14 ± 0.13 vs. 1.45 ± 0.15%/day; 0–4 days: 1.13 ± 0.07%/day vs. 1.47 ± 0.18%/day; 0–8 days: 1.03 ± 0.09%/day vs. 1.40 ± 0.11%/day). SPS remained unchanged. Therefore, D2O has unrivaled utility to quantify day-to-day MPS in humans and inform on short-term changes in anabolism and presumably catabolism alike.